Classification of deep burn injuries--analyses of 117 cases - Liou, X Y; Wang, Y; Wang, T J; Yu, D C; Wang, S B (Acta chirurgiae plasticae, 1993)
A new system of classification, index of deep burn injuries (IDBI), was proposed in this paper. Using this system, we investigated 304 burn sites in 117 cases, of which 94.1% were repaired with the GCM with a satisfactory result. The IDBI of the 304 burn sites is in direct proportion to the severity and extent of burn injury and inverse ratio to the results. Analyses performed in this group suggested that the IDBI has many significances, which include: 1, making a correct diagnosis; 2, providing decided repair indications; 3, indicating the prognosis; 4, providing a reliable method for further investigation in the burn field. The standard of IV degree burn is equal to or more than 2 of IDBI.
Keywords: mužské pohlaví; Male; Humans; Female; kojenec; lidé; Middle Aged; ženské pohlaví; lidé středního věku; Infant; mladiství; Child; dítě; Burns; Adolescent; popálení; dospělí; Child, Preschool; Adult; předškolní dítě